Relationship between ultrasonographically low-echoic lesions under the skin, wheelchair sitting time, and interface pressure on ischial region in individuals with chronic spinal cord injury. (2nd November 2021) - Kawasaki, Shinji; Nishimura, Yukihide; Kamijo, Yoshi-ichiro; Uenishi, Hiroyasu; Nakamura, Taro; Kouda, Ken; Koike, Yumi; Nakamura, Takeshi; Tajima, Fumihiro
Abstract : Objective: To determine the relationship between physical findings, wheelchair sitting time, and interface pressure on ischial region in subjects with spinal cord injury (SCI). Design: Cross-sectional study. Setting: Rehabilitation center in Japan. Participants: Manual wheelchair users with chronic SCI ( n  = 45). Interventions: Pressure ulcers (PU) were diagnosed by inspection, palpation, and ultrasonography. Self-reports were obtained on wheelchair sitting time and pressure mapping was recorded while the subject was seated on the wheelchair. Outcome measures: Subjects were divided into those with ultrasonographically low-echoic lesions (PU-positive group, n  = 11) and no such lesions (PU-negative group, n  = 34). Outcome measures included wheelchair sitting time and interface pressure at bilateral ischial regions. Results: Using ultrasonography, 13 low-echoic lesions were identified in 11 subjects of the PU-positive group. The pressure duration was longer and interface pressure was significantly higher in subjects of the PU-positive group compared with those of the PU-negative group ( P  < 0.05 and P  < 0.001, respectively). Conclusions: This is the first study to evaluate the interrelationship between physical findings, sitting time, and ultrasonographically measured interface pressure on ischial region area in subjects with spinal cord injury. To prevent pressure ulcers, we recommend avoidance of prolonged wheelchair sitting and measures that can reduce the interface pressure. These variables should be carefully tailored to the needs of the individual subjects with SCI.